MANAGEMENT AUDIT TO ASSES THE EFFECTIVENESS OF HUMAN RESOURCE FUNCTION (A Case Study of RSUD Dr. Soeroto Ngawi) - Hika Desyana; Tuban Drijah Herawati (Jurnal Ilmiah Mahasiswa FEB, 2014)
Management audit of human resource function at RSUD Dr. Soeroto Ngawi aimed to asses the effectiveness of human resource function at RSUD Dr. Soeroto Ngawi and to identify its weaknessess by also giving recomendation to solve it. The method used in this research was a descriptive qualitative with case study approach.    Data in this research are obtained from interview, documentation, and questionnaire. The data were then analysed qualitatively. This research focused on eleven (11) human resource functions, they were Plan of Human Resource, Procedure and Recruitment Process of Human Resource, Selection of Human Resource, Orientation and Placement of Human Resource, Training and Development of Human Resource,  Career Development Plan Function Achievement Evaluation, Performance Appraisal, Compensation Management System, Employers Protection, Job Satisfaction and Termination of Employment.Based on the result of the research, ten (10) out of eleven (11) human resource functions run effectively, they were Plan of Human Resource, Procedure and Recruitment Process of Human Resource, Selection of Human Resource, Orientation and Placement of Human Resource, Training and Development of Human Resource, Career Development Plan Function Achievement Evaluation, Performance Appraisal, Employers Protection, Job Satisfaction and Termination of Employment. However, one (1) human resource function was not run effectively, it was Compensation System Management. Based on the weknesses found, the reseracher gave some recommendation for RSUD Dr. Soeroto Ngawi as part of consideration in running the human resource function effectively.Key Words: Management Audit, Human Resource Function, Effectiveness, Recomendation.